Meningkatkan Kualitas Hidup dengan Memanfaatkan Beberapa Gigi Asli yang Tersisa Melalui Desain Swing-Lock Removable Denture - Sutanto, Dahlia (Zenit, 2014)
It should come as no surprise that tooth loss and age are linked. It has been documented that there is a specific tooth loss relationship with increasing age because some teeth are retained longer than others. There is an interarch difference in tooth loss, with the maxillary tooth loss beforemandibular teeth. There is also an intraarch difference with posterior teeth loss before anterior teeth.Frequently, the last remaining teeth in the mouth are the mandibular anterior teeth, sometimes accompanied by compromised conditions, and it is a common finding to see an edentulous maxilla opposing mandibular anterior teeth2. The swing-lock removable partial denture concept offers a wayof maximizing the retention and stability of the removable partial denture and may be very useful in restoring the extremely compromised dentition4. The retentive and stability denture enhance the quality of life by serving esthetic, mastication, and phonetic functions.Keywords: swing-lock removable partial denture, esthetic, mastication, and phonetic function.